Excuses and Alternatives - Chevarie-Cossette, Simon-Pierre (My University, 2021)
A version of the principle of alternate possibilities (PAP) claims that one is only blameworthy for actions which one was able to avoid. Much of the discussion about PAP concerns Frankfurt’s counterexamples to it. After fifty years of refined debates, progress might seem hopeless. Yet, we can make headway by asking: “what’s our reason for believing PAP?” The best answer is this: lacking eligible alternatives—alternatives whose cost is not too high to reasonably opt for—is a good excuse. Yet, this principle is subject to straightforward counterexamples, unless it is given an epistemicised reading. And in this latter case, it does not support PAP. So, PAP is unsupported, at least for now.
Keywords: PAP eligibility excuses exemptions robustness Frankfurt cases moral luck